Brain-Gut Interactions in IBS - Fichna, Jakub; Storr, Martin (Frontiers in Pharmacology, 2012)
Irritable bowel syndrome (IBS) is a common gastrointestinal (GI) disorder with an estimated prevalence of 10-20%. Current understanding of the pathophysiology of IBS is incomplete due to the lack of a clearly identified pathological abnormality and due to the lack of reliable biomarkers. Possible mechanisms believed to contribute to IBS development and IBS like symptoms include physical stressors, such as infection or inflammation, psychological and environmental factors, like anxiety, depression and significant negative life events. Some of these mechanisms may involve the brain-gut axis (BGA). In this article we review the current knowledge on the possible involvement of the BGA in IBS and discuss new directions for potential future therapies of IBS.